Industrial emissions and pesticides impact on agrobiocenosis biodiversity. - Antonie, Iuliana; Teodorescu, Irina (Contributions to Entomology = Beiträge zur Entomologie, 2006)
This contribution presents the results of a long-term study (1987-2004) on the influence of industrial emissions and pesticides on the surface-dwelling arthropod populations of agricultural fields with crops of cereals, potato, sunflower, cabbage and sugarbeet. Particular attention was given to the insects. The agricultural areas exposed to pollutants were compared with control areas not exposed to the chosen influencing factors. The structure of communities of arthropods in biocenoses affected by pesticides and industrial emissions was strongly affected by the toxic pollutants. The influence on the biodiversity of agro-ecosystems is reflected in the quantative and qualitative structure of the collected samples, by a reduction in the number of species and individuals, differences in the species composition and in the composition of trophic groups as well as by differences in population dynamics. Not only was the number of species and individuals of arthropods on plots exposed to industrial emissions and pesticides consistently reduced, but also the number of higher taxonomic categories (classes, orders, families, genera). Predators were numerically dominant on the control areas, phytophages in the affected plots. The quantative relationship between primary and secondary consumers is a good indicator for the estimation of agro-biodiversity. Aranea and Coleoptera showed a certain resistance to the negative effects of toxic substances, which could be shown by their abundance and frequency of appearance. The structural and functional alterations to arthropod communities as a result of exposure to industrial emissions and pesticides are equally applicable to other taxonomic and trophic categories. They are therefore suitable as indicators for the reduction in biodiversity at the level of complete biocenoses. Reductions in biodiversity have in turn an influence on the productivity and the stability of a biocenosis in both space and time.Keywordsindustrial emissions, pesticides impact, agricultural landscapes, biodiversity.